Redistribution of Individual Pension Wealth to Survivor Pensions: Evidence from a Stated Preferences Analysis - Andries de Grip; Didier Fouarge; Raymond Montizaan (Institute of Labor Economics (IZA), 2019)
Pension schemes in the Netherlands allow workers to redistribute their own pension wealth to increase the survivor pension of their partner. However, due to lacking communication and knowledge of survivor pensions among workers, and also due to the lack of transparent products and choice architecture, redistribution remains limited. This paper uses a stated preferences experiment that is explicitly designed for workers with a partner in the age group of 55 to 65 years to elicit their pension redistribution preferences. We find that, on average, the preferred pension wealth redistribution amounts to 50%. 35% of all individuals have such a preference. 33% of all individuals would prefer less redistribution, and 32% percent prefers to redistribute more pension income to the partner upon one's death. We further show that total family income during working life does not affect the redistribution to survivor pensions. However, the distribution of the contribution to total family income before retirement across partners, as well as the survival likelihood of the partner and the number of years the partner is expected to survive, have a significant causal impact on the preferred pension redistribution decision. The preference for redistribution to survivor pensions also depends significantly on personal characteristics, preferences and social attitude. Males have a significantly stronger preference for redistribution compared to females. Moreover, forward-looking, more risk averse and more altruistic individuals have a stronger preference to redistribute part of their pension wealth to a survivor pension. Finally, in particular when employees have the perception that their partner is more forward looking, they are willing to invest more in a survivor pension.
Keywords: J14; J26; D31; 330; stated preferences experiment; redistribution of pension wealth; survivors pension; economic preferences